2005
DOI: 10.3354/meps305017
|View full text |Cite
|
Sign up to set email alerts
|

Succession of hydrocarbon seep communities associated with the long-lived foundation species Lamellibrachia luymesi

Abstract: The vestimentiferan tubeworm Lamellibrachia luymesi lives for over 250 yr and forms aggregations of hundreds to thousands of individuals at hydrocarbon seep sites in the Gulf of Mexico. A succession model has been proposed where changes in the abiotic environment within tubeworm aggregations lead to shifts in the associated community structure. Here, we test this model using new data from communities associated with 13 tubeworm aggregations. We quantify the temporal scale of succession by using a population-gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
130
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(131 citation statements)
references
References 50 publications
1
130
0
Order By: Relevance
“…Aller, 1980Aller, , 1984Aller and Aller, 1998;Meile et al, 2001;Cordes et al, 2005;Dattagupta et al, 2008). However, only a few studies have quantified the influence of the activity of chemosynthetic biota on benthic fluxes at cold seeps (Wallmann et al, 1997;Haese, 2002;Cordes et al, 2005;Haese et al, 2006).…”
Section: Fischer Et Al: Pore Water Geochemistry Of Cold Seeps Offmentioning
confidence: 99%
See 1 more Smart Citation
“…Aller, 1980Aller, , 1984Aller and Aller, 1998;Meile et al, 2001;Cordes et al, 2005;Dattagupta et al, 2008). However, only a few studies have quantified the influence of the activity of chemosynthetic biota on benthic fluxes at cold seeps (Wallmann et al, 1997;Haese, 2002;Cordes et al, 2005;Haese et al, 2006).…”
Section: Fischer Et Al: Pore Water Geochemistry Of Cold Seeps Offmentioning
confidence: 99%
“…Hensen et al, 2003;Cordes et al, 2005;Haese et al, 2006;Dattagupta et al, 2008). Several studies have demonstrated that the interaction of the transport processes bioirrigation and advection significantly influences pore water profiles and solute fluxes at cold seeps (Wallmann et al, 1997;Haese et al, 2006;Niemann et al, 2006).…”
Section: Schematic Evolution Of the Depth Of The Smt And Sulfate Fluxmentioning
confidence: 99%
“…It forms 1-2·m tall bush-like aggregations that can contain over one thousand individuals, and provide habitat for a wide variety of heterotrophic fauna Cordes et al, 2005a;Cordes et al, 2005b). L. luymesi grows extremely slowly, and has a lifespan of at least 170-250·years (Bergquist et al, 2000;Fisher et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…At present, the chemoautotrophic frenulate worms no longer exist, but the products of seepage, such as carbonate rocks, provide settlement substrates, making this community diverse and densely colonized. This is similar to what has been observed or predicted at lower latitude seeps, where carbonates and the tubes of 10 vestimentiferans provide a substrate for hard bottomed animals such as sponges or cnidarians (Bergquist et al, 2003;Bowden et al, 2013;Cordes et al, 2005). The major difference is that in these studies and models of succession in lower latitude seeps, a major driving force from an active to a senescent or background fauna dominated community, is a cessation or displacement of fluid flow, often accompanied by a decrease in sediment sulfide concentrations.…”
Section: Comparisons To Other Seep Sitesmentioning
confidence: 49%